Evaluation of nutritional status among children aged 7-10 - Sztandera, Paulina; Szczepanowska-Wołowiec, Beata; Kotela, Ireneusz (Journal of Education, Health and Sport, 2017)
Introduction and aim of the study. The prevalence of overweight and obesity among the children and adolescents is particularly dangerous, in 60% of children and adolescents, this problem will occur in adulthood, and also increases the risk of diseases such as: type 2 diabetes, hiprelipidemia, hypertension, or emotional disturbances. The aim of the study was evaluation of nutritional status among children aged 7-10 years old from Masłów and Górno District measured by BMI index. Material and methods The research was conducted in 2015 and 2016among the group of 486 primary school children aged 7-10 from Masłów and Górno District. The child body mass was studied on the Tanita weight, for body height was used the Seca measure system. Based on the results BMI was calculated. In relation to BMI centile charts, based on Olaf’s and Ola’s study, determined whether the child was obese, overweight or underweight. Results. The level of somatic development for the whole group in the study, taking into account the results averaged, is within normal limits. Children who are overweight in the examined group was 14.81%, and obesity occurred in 1.02%. Overweight and obesity more often concerned examined boys, overweight - 17,36%, obesity - 1.65%. Among girls overweight was determined in 12,03% of children while obesity - 0,41%. Conclusion. Most of the girls examined were overweight among 9-year-olds, while the problem in boys usually appeared in 10-year-olds. Obesity was present in 7-year-old girls and 8-year-old boys. There is no statistically significant dependence between categories of BMI - overweight and obesity, underweight andthe norm, and also age. BMI increases with age, so it is reasonable to use centile charts for different age groups of children. Education on nutrition and physical activity among both parents and children is needed.